Prevalence of Pica in Patients on Dialysis and its Association With Nutritional Status - Orozco-González, Claudia N; Cortés-Sanabria, Laura; Cueto-Manzano, Alfonso M; Corona-Figueroa, Beatriz; Martínez-Ramírez, Héctor R; López-Leal, Jorge; Martín-Del-Campo, Fabiola; Rojas-Campos, Enrique; Gómez-Navarro, Benjamín (Journal of renal nutrition, 2019)
Pica could be strongly implicated in nutritional status of patients on dialysis; however, very scarce data are currently available. The objective of this study was to evaluate the prevalence of pica and its association with nutritional status in dialysis patients. This is a cross-sectional study in a tertiary care teaching hospital. Four-hundred patients on dialysis, without previous pica diagnosis or transplant, pregnancy, mental illness, or infection, were included in the study. Pica, according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, was classified as no pica, ice pica, or hard pica. Dialysis Malnutrition Score, 24-hour dietary recall, and biochemical measurements were obtained from patients. As part of statistical analysis, point prevalence and 95% confidence interval of pica were calculated. Comparisons between groups were performed by means of analysis of variance, Kruskal-Wallis test, χ , or Fisher exact tests, as appropriate. A multivariate analysis was performed by multinomial logistic regression. Prevalence of pica was 42% (ice pica, 46%; soil, 29%; two substances, 14%; red brick, 5%; paper, 3%; soap, 2%; and cattle pasture, 1%). Comparing patients with pica (hard pica and ice pica) versus no pica, subjects with pica were of younger age (25 ± 7, 27 ± 9, 30 ± 11 years, respectively), were more frequently educated <9 years (57%, 46%, 30%, respectively), and had longer dialysis duration (36 ± 19, 32 ± 18, 27 ± 16 months, respectively). Patients with pica achieved the recommended calorie and macronutrients intake target less frequently than those without pica (40-64% vs. 66-77%, P <.05). Malnutrition was present in 74% of the whole sample: (1) 67% in no pica group, (2) 80% in ice pica group, and (3) 89% in hard pica group (P = .001). In the multivariate analysis (R , 0.27; P < .0001), malnutrition, C-reactive protein, and lower educational level significantly predicted both ice and hard pica. A worse nutritional status was observed in patients with pica, who additionally were younger, had lower educational level, longer dialysis duration, and worse macronutrient intake routine than patients without pica. Malnutrition, C-reactive protein, and lower educational level significantly predicted both ice and hard pica.